2012
DOI: 10.1021/bm300500y
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Two-Phase System-Derived Biofilms for Bacterial Interaction Studies

Abstract: We describe patterning of bacterial biofilms using polymer-based aqueous two-phase system (ATPS) microprinting protocols. The fully aqueous but selectively bacteria-partitioning nature of the ATPS allows spatially distinct localization of suspensions of bacteria such as Pseudomonas aeruginosa and Escherichia coli with high precision. The ATPS patterned bacterial suspensions form spatially distinct biofilms over time. Due to the fully aqueous and gentle noncontact printing procedures employed, coculture biofilm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 29 publications
0
39
0
Order By: Relevance
“…Two of these formulations were used before for printing mammalian cells [14] while the third was a more viscous formulation used in a recent study for patterning bacterial cells and biofilms on polystyrene or PDMS surfaces [13]. MCF 10a cell monolayers were covered with the DMEM/F12-infused polyethylene glycol (PEG) rich phase of each of the three formulations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two of these formulations were used before for printing mammalian cells [14] while the third was a more viscous formulation used in a recent study for patterning bacterial cells and biofilms on polystyrene or PDMS surfaces [13]. MCF 10a cell monolayers were covered with the DMEM/F12-infused polyethylene glycol (PEG) rich phase of each of the three formulations.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study done by our group [13], we showed that the final size of the DEX spot and, hence, the community formed can be controlled by adjusting the initial volume of the droplet. Here, in this study, this same principle was expanded upon and applied to develop isolated bacterial communities on an epithelial cell layer (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, most studies are performed in systems not resembling food products. Clostridium tetani, Lactobacillus rhamnosus, and E. coli W3110, ML308, and MG1655 were shown to have a preference for the dextran phase in polyethylene glycol-dextran systems (40)(41)(42)(43). Also, in polyvinylpyrrolidone-dextran systems, Lactobacillus rhamnosus and Enterococcus faecium M74 were found preferentially in the dextran phase (42,44).…”
Section: Microscopic Characterization Of G/d Systemsmentioning
confidence: 97%
“…To this end, Yaguchi et al patterned two separate populations of bacteria directly over each other using ATPS bioprinting [35]. Using a PEG/DEX ATPS system, Escherichia coli suspended in DEX were patterned over PDMS substrate and formed a biofilm over 24 h (Fig.…”
Section: Biofilm Coculture With Living Tissuementioning
confidence: 99%